An innovative textbook: design and implementation. (29th November 2016) - Ortega, Rafael; Akhtar‐Khavari, Vafa; Barash, Paul; Sharar, Sam; Stock, M Christine
Summary: Background: The 'flipped classroom' instructional strategy has gained much momentum in educational discourse, yet no single educational offering exists in postgraduate medical education (PME) to systematically replace the lecture element of didactic sessions. This article describes the design and implementation of Clinical Anesthesia Fundamentals, the first known textbook in PME addressing this gap in resources through the integration of full‐length interactive multimedia‐enhanced video lectures. The 'flipped classroom' instructional strategy has gained much momentum in educational discourse Innovation: The textbook was developed in alignment with the content outline for the specialty provided by the American Board of Anesthesiology. Its accompanying video lectures, produced at the Media Lab in the Department of Anesthesiology at Boston University Medical Center (BUMC), cover the topics in each chapter of the textbook and include review questions featuring explanatory feedback. Evaluation: Following a 5‐month trial period at the BUMC Anesthesiology Residency Program, the complete resident class (25 of 25; 100%) participated in an anonymous, Institutional Review Board (IRB) ‐approved, five‐point Likert‐type scale survey assessing an underlying variable of preference for the use of multimedia learning tools. Discussion: Survey results suggest that residents favour technology‐enhanced learning environments in which textbooks are coupled with interactive multimedia, and the 'flipped classroom' approach is employed. Although the development of digital videos requires time and financial investment, the improved accessibility and uniform delivery of didactic content are two positive outcomes. Conclusion: This textbook provides an example for educators wishing to learn how to capitalise on advances in technology to further enhance learning and accessibility. Further studies could address the impact of this approach on the academic performance of residents.